1993
DOI: 10.1021/bi00093a013
|View full text |Cite
|
Sign up to set email alerts
|

Energetic cost and structural consequences of burying a hydroxyl group within the core of a protein determined from Ala .fwdarw. Ser and Val .fwdarw. Thr substitutions in T4 lysozyme

Abstract: In order to determine the thermodynamic cost of introducing a polar group within the core of a protein, a series of nine Ala-->Ser and 3 Val-->Thr substitutions was constructed in T4 lysozyme. The sites were all within alpha-helices but ranged from fully solvent-exposed to totally buried. The range of destabilization incurred by the Ala-->Ser substitutions was found to be very similar to that for the Val-->Thr replacements. For the solvent-exposed and partly exposed sites the destabilization was modest (approx… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
96
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 98 publications
(109 citation statements)
references
References 45 publications
13
96
0
Order By: Relevance
“…These results indicate the stabilizing contribution that the amide-hydroxyl hydrogen bond can make to the enthalpy. Blaber et al (1993) conclude that the introduction of hydrogen bonds into T4 lysozyme does not increase the stability of the protein. However, the destabilization is generally entropic, as indicated by the positive values of AAH" in the table.…”
Section: Comparison To Protein Datamentioning
confidence: 74%
See 2 more Smart Citations
“…These results indicate the stabilizing contribution that the amide-hydroxyl hydrogen bond can make to the enthalpy. Blaber et al (1993) conclude that the introduction of hydrogen bonds into T4 lysozyme does not increase the stability of the protein. However, the destabilization is generally entropic, as indicated by the positive values of AAH" in the table.…”
Section: Comparison To Protein Datamentioning
confidence: 74%
“…Blaber et al (1993) have studied the effects of introducing polar groups within T4 lysozyme in order to determine the energetics and structural consequences of burying a hydroxyl group. From their data and the AC, of the wildtype protein (10.5 kJ K" mol-' [Zhang et al, 1991]), we have calculated AH" of unfolding at the T, of the wild-type protein (51.55 "C) and the difference in the unfolding AH" (AAH" = AH&,,,,,, -AH$i/d.,,,pe) ( Table 7).…”
Section: Comparison To Protein Datamentioning
confidence: 99%
See 1 more Smart Citation
“…The following examples clearly show how powerful our tool might be: our prediction for the protein chain 119LA [35] in the NM215 dataset (with default parameters) reaches accuracy 93% and correlation 0.86, compared to accuracy and correlation results, respectively, of 77% and 0.58 for SABLE [13], 83% and 0.62 for RSA-PRP [20], 80% and 0.56 for SARPRED [14]. Even better, our prediction for the protein chain 1bmv 1 [36] in the RS126 dataset (with default parameters) reaches accuracy 97% and correlation 0.95, compared to accuracy and correlation results, respectively, of 74% and 0.52 for SABLE, 70% and 0.42 for RSA-PRP, 69% and 0.37 for SARPRED.…”
Section: Resultsmentioning
confidence: 99%
“…Matthews and coworkers, for example, have shown that specifically engineered polar and charged residues in the core of T4 lysozyme dramatically deteriorate the protein's stability and function. 20,23 Even though the overall fold of the enzyme was maintained, the protein underwent a substantial loss of function as a result. Similarly, the engineering of small-to-large mutations into the core of a protein also resulted in severely destabilized protein structures.…”
Section: Discussionmentioning
confidence: 99%